A DC chopper‐based fast active power output reduction scheme for DFIG wind turbine generators. Issue 11 (20th April 2021) - Zhu, Jiebei; Deng, Zhaoshun; Yu, Lujie; Li, Suxuan; Qu, Chunhui; Qiu, Wei; Adam, Grain P.; Booth, Campbell
Abstract: Increasing penetration level of renewable energy results in unprecedented operational challenges of AC grids due to generation uncertainty and reduced inertia. In grid emergencies, Fast active Power output Reduction (FPR) is demanded to drop wind turbine generator (WTG) power outputs faster than usual. However, the power mismatch between WTG mechanical power input and reduced electrical power output resulted from FPR can lead to rotor overspeed, which cannot be timely nullified by slow‐responding pitch control. Therefore, this paper proposes a novel FPR scheme for doubly‐fed induction generator (DFIG)‐based WTG through coordinated control of DC chopper and pitch angle. Specifically, the FPR command is executed by DFIG rotor‐side converter control, while rotor overspeed is restricted by triggering the DC chopper to dissipate the mismatched power. The pitch angle is actuated at a maximal rate to eliminate the mismatched power and switch off the DC chopper. The effectiveness of the proposed FPR scheme is verified through comparative simulation studies under FPR command execution and a grid fault. It shows the proposed scheme can achieve FPR in tens of milliseconds, avoid rotor overspeed and provide low‐voltage ride‐through capability in a fully‐controlled manner.